Analisis Kecurangan Laporan Keuangan dengan Perspektif Teori Fraud Hexagon Pada Perusahaan BUMN yang Terdaftar di BEI Tahun 2021 – 2023 - Selviyani Selviyani; Agung Joni Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to obtain factual evidence related to financial statement fraud in state-owned companies that are listed and have published their financial statements on the Indonesia Stock Exchange (IDX) reviewed from the hexagon fraud theory during the period 2021 – 2023. This research study focuses on financial statement fraud with the hexagon fraud theory which includes six pillars that cause fraud, namely pressure, opportunity, rationalization, capability, arrogance, and colllusions. The six pillars are measured by financial targets, financial stability, external pressure, ineffective monitoring, audit change, dualism position, CEO picture, and government project. Meanwhile, fraud in financial statements is measured using the F-Score Model. The sample used in this study was 20 state-owned companies accessed through IDX. Sampling was carried out based on the purposive sampling. The methodology used in the study is a multiple linear regression analysis with the SPSS Version 25. As a result of this study, referring to financial stability, external pressure and arrogance referring to CEO picture triggered interaction with indications of financial report fraud, while opportunity referring to ineffective monitoring, rationalization referring to audit change, capability referring to dualism position, and collusion referring to government projects did not trigger interaction with indications of financial report fraud.